POLISH THINK TANKS’ ACTIVITY IN THE EUROPEAN SOFT POWER POLICY - Grigorev, Alexandr; Grishin, Nikolai; Usmanov, Rafik; Mironova, Yulia (Gênero & Direito, 2020)
The article defines the place of Polish think tanks in the all-European soft power policy. For this purpose, elements of the modified Joseph Nye’s soft power concept were used. The analysis was conducted on the example of four Polish think tanks (Polish Institute of International Affairs (PISM), Center for Eastern Studies (OSW), College of Eastern Europe (KEW) and Warsaw University Institute of Eastern Europe (SEW). The authors’ conclusions allowed determining the place of Polish think tanks in the EU foreign policy as that of organic elements aimed at achieving the goals prescribed by the European Union’s Foreign and Security Policy. At the same time, the activities of Polish think tanks are also aimed at solving the tasks of the Polish Foreign Ministry, namely the expansion of Polish influence in the Eastern European countries and the opposition to those political actors whose activities are contrary to Polish foreign policy.